FROM DATA TO ACTION: THE FUTURE OF DISTRIBUTED TRACING WITH AI IN CLOUD ENVIRONMENTS - Muskaan Mongia, (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This comprehensive article explores the evolution and implementation of distributed tracing in modern cloud environments, focusing on its integration with artificial intelligence and fog computing. The article examines how organizations leverage distributed tracing to address the growing complexity of microservices architectures across cloud and edge environments. This article demonstrates how AI-enhanced distributed tracing significantly reduces incident resolution time and improves anomaly detection capabilities through detailed analysis of performance metrics, implementation strategies, and real-world deployments. article covers key aspects, including serverless analytics integration, open-source tool evolution, and fog computing implementations, providing insights into operational improvements achieved through advanced tracing capabilities. It encompasses technical considerations and business impacts, offering a holistic view of how distributed tracing transforms modern system observability and enhances developer productivity.